Between Women : Friendship, Desire, and Marriage in Victorian England - Marcus, Sharon, 1966- (Book collections on Project MUSE., 2007)
Women in Victorian England wore jewelry made from each other's hair and wrote poems celebrating decades of friendship. They pored over magazines that described the dangerous pleasures of corporal punishment. A few had sexual relationships with each other, exchanged rings and vows, willed each other property, and lived together in long-term partnerships described as marriages. But, as Sharon Marcus shows, these women were not seen as gender outlaws. Their desires were fanned by consumer culture and their friendships and unions were accepted and even encouraged by family, society, and church. Far from being sexless angels defined only by male desires, Victorian women openly enjoyed looking at and even dominating other women. Their friendships helped realize the ideal of companionate love between men and women celebrated by novels, and their unions influenced politicians and social thinkers to reform marriage law.--From publisher description.